2015
DOI: 10.1186/s41043-015-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of household food security and women’s dietary diversity in rural Bangladesh: a cross-sectional study

Abstract: BackgroundThere has been limited decline in undernutrition rates in South Asia compared with the rest of Asia and one reason for this may be low levels of household food security. However, the evidence base on the determinants of household food security is limited. To develop policies intended to improve household food security, improved knowledge of the determinants of household food security is required.MethodsHousehold data were collected in 2011 from a randomly selected sample of 2,809 women of reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
130
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(165 citation statements)
references
References 24 publications
27
130
2
6
Order By: Relevance
“…The difference could be due to the fact that those with land could grow some food which may supplement what they acquire through purchases. This finding is consistent with a study conducted in Bangladesh [21] where land ownership was reported to positively influence women dietary diversity. Vitamin A rich fruits 13 5 Organ meat 10 4 Fish and sea food 4 2 Adjusted for socioeconomic and demographic characteristics (education level, marital status, occupation, household head, level of income, source of lighting, livestock ownership and household assets) and morbidity incidence Findings of this study are in agreement with findings of several other studies which have reported that dietary diversity is associated with socioeconomic status [19,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The difference could be due to the fact that those with land could grow some food which may supplement what they acquire through purchases. This finding is consistent with a study conducted in Bangladesh [21] where land ownership was reported to positively influence women dietary diversity. Vitamin A rich fruits 13 5 Organ meat 10 4 Fish and sea food 4 2 Adjusted for socioeconomic and demographic characteristics (education level, marital status, occupation, household head, level of income, source of lighting, livestock ownership and household assets) and morbidity incidence Findings of this study are in agreement with findings of several other studies which have reported that dietary diversity is associated with socioeconomic status [19,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 83%
“…For instance, a study by Vakili et al [25] in Ahvaz-Iran showed a significant relationship between DDS and the economic situation of the respective respondents (p < 0.05). Similarly, another study in Bangladesh found significant association between relative wealth, land ownership, livestock ownership and women dietary diversity [21]. It is evidently clear from the present study that women of a higher socioeconomic status had a higher DDS as compared to women of a lower socioeconomic status.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, the HHDS average was of 6.89, a result that differs from the ones found by De Cock et al (2013) in Limpopo province, South Africa. They reported that the households had an average HDDS of 4.5, whereas Harris-Fry et al (2015) in their research performed with women from the rural area of Bangladesh reported an average of 3.8 food groups. However, what the HDDS means in terms of public health is not clear, since there is no specific cut points (Swindale and Bilinsky, 2006;FAO, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Food security can be estimated by per capita calorie intake availability method, food expenditure method, food-grain availability method, food-deficit method, dietary food energy supply technique, food energy deficiency and diet quality method at individual level [35,40,43,44,55,[63][64][65][66][67][68][69][70][71][72][73][74][75][76]. Food inequality across individuals and households can be measured by headcount ratio, Simpson and Shannon index methods.…”
Section: Measurement Of Food Securitymentioning
confidence: 99%
“…Harris Fry H et al [75], concluded that wealth and land ownership were the crucial factor to reduce the food insecurity in Bangladesh. Zou J et al [93], found that China's food security is negatively impacted due to redistribution of land resources, rising international food prices, declining water resources, growth in food demand.…”
Section: Association Of Fsi With Socio-economic Factorsmentioning
confidence: 99%